Comparative Levels of Waxy Gene Product of Endosperm Starch Granules of Different Rice Ecotypes - Villareal, C.P.; Juliano, Bienvenido O. (Wiley, 1989)
Starches of 40 rice varieties from different ecosystems and 2 amylose extender mutants were analyzed for their predominant waxy gene allele (Wxa or Wxb) through the amount of Wx gene product (60‐kdal polypeptide) by SDS‐polyacrylamide gel electrophoresis. Nonwaxy rices carrying the Wxa and Wxb alleles were clearly differentiated by two distinct regression equations correlating AC and the amount of Wx gene product. Indica, samba, and tropical upland rices hat the Wxa allele and contained about three times as much Wx gene protein at the same AC as japonica and long‐grain US rices carrying the Wxb allele. Indica‐japonica, bulu, and basmati‐type rices showed selection for either Wxa or Wxb. Identification of the predominant Wx allele provides an alternative method for classifying nonwaxy rice grains into indica or japonica type, and complements the embryo isozyme classification. Results of the two methods are generally consistent.